Climbing the Ladders of Job Satisfaction and Employees' Organizational Commitment: A Semi-Nonparametric Approach - José António Cabral Vieira (Institute of Labor Economics (IZA), 2019)
Researchers and human resource practitioners are nearly unanimous that satisfied and committed employees can play a major positive role in business performance. There is, however, a need for further evidence on what determines satisfaction at the workplace and how it can be promoted. In other words, do managers have access to specific satisfaction-enhancing variables, or are the determining factors more intrinsic to workers, such as their demographics or even religious beliefs and practices? Furthermore, is employee commitment totally explained by satisfaction, or do further factors promote it? This paper addresses these topics using an extensive sample of employees from a large number of countries. For this purpose, we use a semi-nonparametric estimator for a series of generalized models that nest the conventional ordered probit model, thus relaxing the distributional assumption in that model. The main results indicate that not all determinants of employees' satisfaction can be fostered by management, although some managerial instruments are available. Moreover, promoting workplace satisfaction helps increase employees' commitment (and consequently business success) but does not fully exhaust the explanation of such behavior. The findings of this study can motivate further study among researchers and illuminate helpful practices for human resource managers and practitioners.
Keywords: J50; J53; 330; job satisfaction; organizational commitment; worker characteristics; job characteristics; ordered probit; semi-nonparametric estimation